ANALYSING EFFICIENCY OF MULTIPATH ROUTING ON REACTIVE ROUTING PROTOCOLS IN MANET - Atri, Jaideep; Upadhyaya, Shuchita (International Journal of Computer Sciences and Engineering, 2025)
The mobility of the nodes is an important factor in Mobile Ad hoc Networks (MANETs). The reactive routing protocols are very useful to deal with the mobility of nodes. In the Reactive routing or On Demand protocol the transmission of data is always preceded by the process of finding the route. So these protocols can effectively deal with the stale routes arising due to the mobility of nodes. Examples of such protocols include Dynamic source routing protocol (DSR), Ad-hoc On demand Distance Vector Routing protocol (AODV) etc. The reactive protocols can further be categorized as Unipath and Multipath routing Protocols. The AODV is Unipath routing protocol whereas multipath variant of AODV is Ad hoc On demand Multipath Distance Vector Routing Protocol (AOMDV). Here the efficiency of both AODV and AOMDV has been tested using NS2 simulator for different number of nodes moving at different speeds with respect to different performance metrics